Effect of ultraviolet accelerated aging on mechanical and optical properties of polycarbonate - SUN Qi-wei (Journal of Materials Engineering, 2021)
In order to explore the effect of accelerated UV aging on the mechanical and optical properties of polycarbonate, the changes of polycarbonate's transmittance, yellow index, tensile properties and flexural properties with aging time and radiation intensity were studied by using the method of exposure to laboratory fluorescent ultraviolet lamps source. The results show that the light transmittance of polycarbonate is decreased with the increase of UV aging time and radiation intensity. According to FT-IR, several colored groups are created in polycarbonate because of prolonging the aging time and increasing the radiation intensity, which affects the optical property of polycarbonate. The tensile strength and elongation at break of polycarbonate are decreasd with the increase of UV aging time and irradiation intensity. The microcracks and holes on surface of polycarbonate are produced by longer aging time and higher radiation energy, which expand under tensile load and cause fracture. The flexural strength of polycarbonate is increased with the increase of UV aging time and irradiation intensity if the testing surface is irradiated. The degradation layer formed on the surface of the material increases the stiffness of polycarbonate, which leads to the increase of strength. The tensile modulus and bending modulus of polycarbonate are less affected by aging time and irradiation strength because UV accelerated aging has little effect on molecular weight.